Diagnostic, therapeutic and prognostic considerations in traumatic amenorrhea - Bettinotti, Alberto (2015)
The purpose of this communication is precisely calling attention to the finding of these intracavitary synechiae to formulate some diagnostic considerations and in particular to express our view on the treatment and prognosis of this gynecological process much impact on the menstrual cycle, pregnancy and infertility.